Advanced Glycation End Products (AGEs): Biochemistry, Signaling, Analytical Methods, and Epigenetic Effects. (18th March 2020) - Perrone, Anna; Giovino, Antonio; Benny, Jubina; Martinelli, Federico
Abstract : The advanced glycation end products (AGEs) are organic molecules formed in any living organisms with a great variety of structural and functional properties. They are considered organic markers of the glycation process. Due to their great heterogeneity, there is no specific test for their operational measurement. In this review, we have updated the most common chromatographic, colorimetric, spectroscopic, mass spectrometric, and serological methods, typically used for the determination of AGEs in biological samples. We have described their signaling and signal transduction mechanisms and cell epigenetic effects. Although mass spectrometric analysis is not widespread in the detection of AGEs at the clinical level, this technique is highly promising for the early diagnosis and therapeutics of diseases caused by AGEs. Protocols are available for high-resolution mass spectrometry of glycated proteins although they are characterized by complex machine management. Simpler procedures are available although much less precise than mass spectrometry. Among them, immunochemical tests are very common since they are able to detect AGEs in a simple and immediate way. In these years, new methodologies have been developed using an in vivo novel and noninvasive spectroscopic methods. These methods are based on the measurement of autofluorescence of AGEs. Another method consists of detecting AGEs in the human skin to detect chronic exposure, without the inconvenience of invasive methods. The aim of this review is to compare the different approaches of measuring AGEs at a clinical perspective due to their strict association with oxidative stress and inflammation.